Undiagnosed term abdominal pregnancy in a district-level hospital of a developing country: a miracle baby - Win Win Than; DG Marshitah Binti PG Baharuddin; M Tanveer Hossain Parash; , Aung Mra (https://pubmed.ncbi.nlm.nih.gov/36945266/, 2023)
Term abdominal pregnancy is a sporadic ectopic pregnancy associated with high maternal and perinatal morbidity and mortality. As symptoms are non-specific and resemble those of other ectopic pregnancies, early diagnosis is the major challenge in poor health setups. A 24-year-old primigravida at 38 weeks gestation was planned to undergo a cesarean section for the transverse lie. Abdominal pregnancy was accidentally discovered during the cesarean section, and a healthy, normal baby boy was delivered. The placenta was attached to the greater omentum, so its removal required omentectomy without compromising the blood supply to the bowels. Both patient and her baby boy were discharged on the seventh day without complications. No congenital anomalies were detected in the baby. In a term abdominal pregnancy, the most significant challenges are the control of bleeding and the decision on placenta removal, followed by prompt delivery of the fetus. Therefore, along with the gynecologist, the availability of trained personnel, such as anesthetists, pediatricians, and general surgeons, is necessary for a successful management outcome.